Plasmonics: Terahertz Localized Surface Plasmon Resonances in Coaxial Microcavities (Advanced Optical Materials 6/2013). Issue 6 (19th June 2013) - Withayachumnankul, Withawat; Shah, Charan Manish; Fumeaux, Christophe; Kaltenecker, Korbinian; Walther, Markus; Fischer, Bernd M.; Abbott, Derek; Bhaskaran, Madhu; Sriram, Sharath
<x xml:space="preserve">Abstract</x> Coaxial microcavities etched into the surface of a heavily‐doped silicon substrate by W. Withayachumnankul, S. Sriram, and co‐workers are shown on page 443 to support localized surface plasmon resonances at terahertz frequencies through the interplay between the cylindrical surface plasmon polaritons and the cavity modes. The coaxial geometry partly determines the resonance frequency, as illustrated by the absorption map. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>